Effect of milling capability in the kinetics of cyanudation for a preconcentrate of Au-Cu - Barzola, Edwin (2011)
The pre-concentrate of Au-Cu from a gravimetric concentrator FALCON was subjected to different treatment processes in order to separately extract the copper and then the gold, without having success; after some attempts, it was achieved to recover the gold from the correlation of the milling capability and cyanidation, recovering very encouraging tenors through the application of models of milling batch proposed by Magne, Austin and Concha, and for the cyanidation, it was applied the Kinetic Nucleus Recessive Model with the following offered configuration: 1 -2α/3 – (1-α)2/3= 3.30*10-10(0.015 + 0.0006TM) *(TM)5.5124*t The concentrate sample with around 10 Oz. of gold per ton and 2.50% of copper, tested in a milling to 96% - 200 nets and leached with 0.4% of cyanide for 70 hours obtained recoveries higher than 95%, with an average consumption of 46 Kg. of cyanide per ton of mineral.